Intra and inter test repeatability of accelerometric indicators measured while running - Provot, T.; Munera, M.; Bolaers, F.; Vitry, G.; Chiementin, X. (Procedia Engineering, 2016)
Recently the use of Inertial Measurement Units (IMU's) has been extended to several applications in human activity. In running, several studies show the possibility of using IMU's to measure different indicators of speed and foot strike. However, few studies describe the repeatability of those indicators. In this context, the aim of this study is to analyse the intra and inter test repeatability of several temporal and spectral indicators using an IMU under constant running conditions. Accelerations were measured using three IMU's mounted on the trunk near the lumbar, the right tibia and the dorsal surface of the right shoe above the metatarsals. The subject follows two different protocols to realize the intra test and the inter test repeatability of eight different parameters: root mean square (RMS) values of acceleration, kurtosis, total energy, median frequency, mechanical stiffness, mean stride duration, contact and flying duration. For all parameters the mean, standard deviation and coefficient of variation were computed for each set of test. The coefficient of variation was lower than 5% for both test for all parameters except kurtosis and the median frequency. Parameters with acceptable value at constant conditions of surface and speed can be used as an indicator to compare several conditions, such as the influence of speed, surface or anthropometry of the subjects.